POTENTIAL ANTIOXIDATIVE AND ANTIFUNGAL ACTIVITIES FROM Eugenia polyantha WIGHT - Raden Arthur Ario Lelono (Pusbindiklat - LIPI, 2012)
Antioxidative activities of Eugenia polyantha Wight bark extracts grown in Indonesia were evaluated using 2,2-diphenyl–1-picrylhydrazyl radical-scavenging, β-carotene bleaching assay, and thiobarbituric acid reactive substance (TBARS) assay. The extracts also showed protection towards lipid peroxidation on cooked (68%) and raw meat (56%). The methanol-water extract showed the highest level of free radical-scavenging activity ((ED50) = 0.18 mg/ml) and protection from β-carotene bleaching (85.7% at 100 μg/ml). The extracts showed the highest total phenolic content (856 mg gallic acid equivalent (GAE)/g and 161 mg catechin equivalent (CE)/g) and total antioxidative capacity (449 mg ascorbic acid equivalent (AAE)/g). A relationship between total antioxidative capacity and total phenolic content was recognized from E. polyantha bark extracts. Furthermore E. polyantha essential oil demonstrated inhibition growth activity of several agricultural pathogenic fungus i.e., Pleurotus ostreatus (46.2%), Fusarium oxysporum (38.1%), and Coreynespora cassicola (32.2%).